Peningkatan Hasil Belajar Tema Benda di Sekitarku Melalui Metode Pembelajaran Project Based Learning Kelas III SDN Rejosari 03 - Setiawan, Odditya (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This research was motivated by the monotonous and boring state of online learning in class III. Teacher Student learning outcomes also show an average below the KKM. Formulation of the problem "How is the management of learning the theme of objects around me through Project Based Leraning for third grade students of SDN Rejosari 03? The purpose of describing the learning management of the theme of objects around me through the Project Based Learning method in class III Classroom action research methods The research sample is class III. The instrument uses observation and tests using the Project Based Learning model, 2 cycles. Based on the research, there was an increase in student learning outcomes both in activities and learning outcomes, the average score of students was as follows: Cycle I 75.42% with a percentage of 75%, cycle II 93.75% with a percentage of 100%. It can be concluded that learning the theme of 3 objects around me by using the Project Based Learning learning model, the results of student learning tests experienced an increase in each cycle. The researcher recommends the principal, teachers and related staff in order to develop the quality of learning in the classroom using the PBL learning model.